A influência do marketing ambiental na decisão de compra dos consumidores de produtos orgânicos - Mattos, Kandy Maria da Costa (2009)
The search of the man for more comfort and one better quality of life led to an increment of the production of goods and services, that results, almost always, in aggressions to the nature and to a reduction of this same quality of life. The concern with the ambient problems appears as an important element regarding the material and economic growth and of the quality of life. With this scene a new question, the Ambient Marketing appears. Although the marketing concept to be well ample, the companies use the term ambient marketing to make reference what in fact, many times, are a more specific activity of ambient communication. The ambient communication is a new form to communicate used for the companies with the objective to get advantages of its competitors ahead, since the competitiveness by means of the o price, the stated period and the quality if becomes extremely incited. In view of the current competitive market, where the organizations need distinguishing to get greater have detached front to the competition, and the fact of the society to be each time more worried about the environment and the impacts that the companies cause it, the ambient communication has been used as form to convince its customers. Of this form, she evaluated herself, through a exploratory research and qualitative, the influence of the use of the ambient communication in the decision of purchase and of that she forms the companies when using of this communication can add value to its product. The results had indicated that 77% of the interviewed ones had heard to say on marketing or ambient communication and that the television is main the media for this knowledge, a time that 90.9% of the respondents had affirmed to have seen propagandas of directed products of consumption to the ambient question in this way. In fact, the concern with the environment demonstrated for the companies has its impact, therefore 84% of the respondents had told if to sensetize with this fact. However, only a lesser number of people, 70.5% answered that this concern really influences in its decision of purchase